2017
DOI: 10.1097/igc.0000000000000927
|View full text |Cite
|
Sign up to set email alerts
|

Combined Oral Medroxyprogesterone/Levonorgestrel-Intrauterine System Treatment for Women With Grade 2 Stage IA Endometrial Cancer

Abstract: Combined oral MPA/LNG-IUS treatment is considered to be a reasonably effective fertility-sparing treatment of grade 2 stage IA endometrial cancer. Although our results are encouraging, it is preliminary and should be considered with experienced oncologists in well-defined protocol and with close follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 19 publications
4
55
0
Order By: Relevance
“…The overall complete remission rate was 87.5% (14/16), and the average time to complete remission was 9.8±8.9 months (range 3–35 months) 28. Hwang et al studied five patients with endometrioid endometrial cancer treated with combined oral medroxyprogesterone acetate and levonorgestrel-release intra-uterine devices, with a complete response in three out of five patients 42. Thus, concurrent treatment might have a better response rate than single agent management.…”
Section: Discussionmentioning
confidence: 99%
“…The overall complete remission rate was 87.5% (14/16), and the average time to complete remission was 9.8±8.9 months (range 3–35 months) 28. Hwang et al studied five patients with endometrioid endometrial cancer treated with combined oral medroxyprogesterone acetate and levonorgestrel-release intra-uterine devices, with a complete response in three out of five patients 42. Thus, concurrent treatment might have a better response rate than single agent management.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the incidence of EC is rising yearly ( 1 ). According to statistical data, the morbidity of EC ranks second among female reproductive tract tumors, second only to cervical cancer ( 2 ). It has been found that EZH2 is a core component of the family of Polycomb group proteins ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Conservative treatment of endometrial adenocarcinoma traditionally involved oral progestin therapy; more recently, many reports have introduced LNG-IUS alone or combined with GnRHa or oral progestin as an alternative to oral systemic progestin alone for the treatment of women with EC and AH (24,(27)(28)(29)(30). Brown et al (24) in 2012 reported a case of an 18-yearold girl with grade 2 endometrioid adenocarcinoma, treated with LNG-IUS successfully.…”
Section: Discussionmentioning
confidence: 99%
“…Brown et al (24) in 2012 reported a case of an 18-yearold girl with grade 2 endometrioid adenocarcinoma, treated with LNG-IUS successfully. Hwang et al (27) evaluated the efficacy of combined MPA/LNG-IUS treatment for grade 2 stage IA EC; the CR rate was 60% (3/5), and one patient (13.3%) who relapsed after 14 months achieving CR received combined therapy and achieved CR by 6 months again. A prospective observational study showed that for grade 1 EC, combined oral MPA/LNG-IUS treatment was more effective than oral progestin alone (31).…”
Section: Discussionmentioning
confidence: 99%